Two new sesquiterpene lactones from the fruits of Illicium jiadifengpi. Issue 3 (1st February 2016) - Liu, Jifeng; Liu, Feiyan; Zhang, Nenling; Wang, Yafeng; Yang, Lijia; Bi, Yuefeng; Zhang, Yanbing; Liu, Mengqi
Abstract : Two new seco -prezizaane-type sesquiterpenes, 3, 4-dehydroneomajucin (1 ) and 1, 2, 3, 4-tetradehydroneomajucin (2 ), were isolated from the fruits of Illicium jiadifengpi . The structure of these compounds was determined using 1D and 2D NMR and ESI-MS. The isolates were evaluated for their anti-hepatitis B virus activities on the Hep G2.2.15 cell line. The inhibitory rates of compounds1 and2 on the HBeAg and HBsAg expression were 30.08 ± 3.09% and 11.43 ± 1.92% at a concentrations of 68.00 μM and 7.88 ± 1.21% and 16.96 ± 4.24% at a concentration of 68.50 μM, respectively. Abstract :